Knowledge and Practice of Family Planning Device in Betkot Muncipality, Kanchapur District - Bhatt, Shatya Narayan (Rural Development Journal, 2019)
The challenging problem of population growth attracts everyone to find the solution. Since governmental and non-governmental policy and programs had lunched the growth rate did not reduce hopefully. So, it is necessary to study about knowledge, and practice of Family Planning devices. This study entitled “Knowledge and Practice of Family Planning devices among married women in Betkot Municipality, Kanchanpur District.” Is based on primary data collection from probability sampling method, covering 160 respondents was out of 800 married population reproductive age group (15-49). The main objective of the study is to examine the knowledge on use of Family planning devices among married women aged 15-49 years, to find out the practice of family planning devices among the respondents. Out of 160 respondents, 80 percent women are literate and 20 percent are illiterate. The major occupations of the respondents are agriculture and labor. 34.47 % respondents are engaged in the agricultural activities and followed by 29.95 % wage labor. Similarly, 23.73 % of respondents are house wife, 3.95 % are engaged on service and 5.08 % are engaged on others activities. The result of 85.62% respondents have ever used of any contraceptive devices, whereas 14.37% were not using any of those. There is strongly positive relationship existed between use of family planning method and socio-economic and demographic variables like education status of women and number of living children. To avoid pregnancy and Partners insisted are the main reason for using family planning method. Side effect, desire for son /daughter and husband and family disagreement are the most important reason for not using family planning devices.